2006
DOI: 10.4161/cbt.5.12.3352
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the short form of cFLIP by RNA interference is sufficient to enhance TRAIL sensitivity in PC3 prostate carcinoma cells

Abstract: The pro-apoptotic death receptor ligand tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has received significant attention as a novel cancer therapeutic, since it selectively induces apoptosis in malignant and not normal cells. Unfortunately, prostate cancer cells display little if any susceptibility to TRAIL-induced apoptosis. However, sensitivity to TRAIL is enhanced by doxorubicin, which correlated with a decrease in expression of the caspase-8 inhibitor cFLIP (Kelly et al., Cancer Biol Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…The hydrogen peroxide dose curve indicates that at doses as low as 25 μM, the protein profile of doxorubicin treatment is recapitulated. This profile, as we have shown in previous work [13] and in Figure 3B, is characterized by a reduction in cFLIP S , preservation of cFLIP L and strong phosphorylation of EF-2. We therefore hypothesized that hydrogen peroxide could, like doxorubicin, sensitize PC3 cells to TRAIL.…”
Section: Free Radicals Can Phosphorylate Ef-2 and Reduce Cflip S Exprsupporting
confidence: 56%
See 4 more Smart Citations
“…The hydrogen peroxide dose curve indicates that at doses as low as 25 μM, the protein profile of doxorubicin treatment is recapitulated. This profile, as we have shown in previous work [13] and in Figure 3B, is characterized by a reduction in cFLIP S , preservation of cFLIP L and strong phosphorylation of EF-2. We therefore hypothesized that hydrogen peroxide could, like doxorubicin, sensitize PC3 cells to TRAIL.…”
Section: Free Radicals Can Phosphorylate Ef-2 and Reduce Cflip S Exprsupporting
confidence: 56%
“…For instance, we have recently shown that downregulation of cFLIP S was sufficient to sensitize PC3 cells to TRAIL [13]. Because these cells have such low levels of Bcl-2 and Mcl-1, cFLIP S may be the critical determinant of its apoptotic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations